Induction of Suppressive Soil in the Management of Fusarium Wilt on Banana Seedlings - Ting, Adeline Su Yien (2001)
This study detennined the potential of using artificially 'induced' suppressive soil to suppress the development of Fusarium wilt on susceptible banana seedlings (cultivar Berangan). Trichoderma harzianum (UPM 40) was selected as the microbial antagonist, and calcium nitrate (Ca(N03)2) as the soil amendment. Both biotic and abiotic components, respectively, were incorporated into the soil to mimic the contents of naturally existing Fusarium suppressive soils. The potential of T harzianum as a biocontrol agent was confirmed from the series of antagonism tests, with positive results in lysis, antibiosis and mycoparasitism tests. In vitro tests detennined that T harzianum required early establishment prior to challenge with Fusarium oxysporum f. sp. cubense race 4 (FocR4), to ensure effective antagonistic activity. Both T harzianum and FocR4 tolerated pH 5-8, and Ca2+ concentrations within 5-750 ppm. Soil pH was not affected by Ca(N03)2 application, indicating compatibility of inoculating T. harzzanum together with Ca(N03)2 application When tested on Berangan seedlings in the glasshouse, treatment with Ca(N03)2 alone provided better disease suppression compared to treatment with both T. harzzanum and Ca(N03h, and treatment with T. harzzanum alone. Treatment with Ca(N03)2 alone recorded low disease incidence (DI) of 5 1 % as compared to 59% and 69% from combined treatments and T. harzzanum alone, respectively, 8 weeks after inoculation. Calcium reduced the population of FocR4, promoted plant growth, and induced host resistance through increased peroxidase and polyphenoloxidase activity, and phenol content. Increased in enzymatic activities and phenol content was related to extensive cell wall lignification as revealed by histological observatlOns, resulting in resistance to FocR4 hyphal penetration. The formation of Ca-pectate also contributed to host resistance. Biocontrol efficiency of T. harzzanum was dependent on soil environment, as the glasshouse trial did not suppress disease incidence, contrary to its antagonistic effect in In vztro tests. T. harzzanum did not induce host resistarce, instead, predisposed the seedlings to infection by increasing root growth and infection sites. Disease suppression achieved through treatment with Ca(NE)3)2 was dependent on Ca2+ availability in the soil and Ca2+ content in the plant tissues. A more frequent application using suitable rates is then suggested as follow-up studies.